2012
DOI: 10.3892/ijo.2012.1353
|View full text |Cite|
|
Sign up to set email alerts
|

The anti-obesity drug orlistat promotes sensitivity to TRAIL by two different pathways in hormone-refractory prostate cancer cells

Abstract: Abstract. The administration of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is one of the expected cancer therapeutics. However, improvements are required in therapies against TRAIL-resistant tumor cells. We report, here, that the anti-obesity drug orlistat enhances the sensitivity to TRAIL in hormone-refractory prostate cancer (HRPC) cells through two different pathways. The combination of orlistat and TRAIL remarkably induced apoptosis in TRAIL-resistant HRPC, DU145 and PC3 cells. Orlista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…AICAR has also been implicated in the potentiation of ROS production induced by high glucose levels in pancreatic beta cells [Kim et al, 2007]. Fujiwara et al reported that Orlistat induced ROS production in DU145 and PC3 PCa cells [Fujiwara et al, 2012]. We report here that a dose range of 0.5–3 mM of AICAR has non-significant effects on all three PCa cell lines tested (PC3, DU145, LNCaP) for a 24 h time point.…”
Section: Discussionmentioning
confidence: 49%
“…AICAR has also been implicated in the potentiation of ROS production induced by high glucose levels in pancreatic beta cells [Kim et al, 2007]. Fujiwara et al reported that Orlistat induced ROS production in DU145 and PC3 PCa cells [Fujiwara et al, 2012]. We report here that a dose range of 0.5–3 mM of AICAR has non-significant effects on all three PCa cell lines tested (PC3, DU145, LNCaP) for a 24 h time point.…”
Section: Discussionmentioning
confidence: 49%
“…Consequently, one of the upcoming anticancer chemotherapeutic regimens depends on inhibition of FASN [10–14,16,17]. We and others have demonstrated that exposure of tumor cells to orlistat, a FASN inhibitor; can manifests tumor-specific cytotoxicity [1822]. Moreover, impact of FASN inhibition on cell survival displays cell-specific variations [8].…”
Section: Introductionmentioning
confidence: 99%
“…Biologically active phytochemicals isolated from medicinal plants or their crude extracts have been reported to enhance TRAIL-induced apoptosis via CHOP-dependent DR5 upregulation in cancer cells [ 21 , 29 ]. In addition to the CHOP-dependent pathway, CHOP-independent DR5 upregulation has been observed in certain cancer cells treated with TRAIL and other chemicals, such as Orlistat (Xenical TM ) [ 44 ] and curcumin [ 45 ], although the key mediators of DR5 upregulation have not been identified.…”
Section: Discussionmentioning
confidence: 99%